A concise introduction to world religions - Amore, Roy C.; Hussain, Amir; Oxtoby, Willard G. (Oxford University Press, 2020)
Based on the best-selling World Religions: Eastern Traditions and World Religions: Western Traditions, A Concise Introduction to World Religions, Fourth Edition, is ideal for single-semester courses. Renowned contributors trace the origins and evolution of the major traditions, explain their essential teachings, outline their practices, and examine their interactions with modern culture and society, while insightful introductory and concluding essays suggest countless avenues for further reflection and study.